2003
DOI: 10.1002/ffj.1190
|View full text |Cite
|
Sign up to set email alerts
|

Use of gas chromatograms of the essential leaf oils of the genus Eucalyptus for taxonomic purposes: E. subser. Euglobulares (Blakely)

Abstract: Leaves were harvested from 37 trees of Eucalyptus subser. Euglobulares Blakely, E. globulus Labill., E. bicostata Maiden, Blakely and Simmonds, E. maidenii F. Muell. and E. pseudoglobulus Naudin ex Maiden, selected from six sites around Australia: both native-growing and cultivated taxa were chosen. Volatile leaf oils were isolated by vacuum distillation and analysed by GC (one tree was previously analysed by GC-MS). The conditions of distillation and analysis were maintained throughout this study. Many of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Many investigations have been done on the volatile components of essential oils from different species of Eucalyptus . Moreover, there are many reports which have determined the composition of essential oils from the leaves [13,14], immature flowers [8] and recently from the fruits [5]. Previous studies of the composition of Eucalyptus oleosa leaves essential oil have been reported [9,15,16], but to the best of our knowledge, no previous studies on the chemistry and antioxidant and antimicrobial activities of the essential oils of stem, immature flowers and fruit of E. oleosa have been presented in the literature to date.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations have been done on the volatile components of essential oils from different species of Eucalyptus . Moreover, there are many reports which have determined the composition of essential oils from the leaves [13,14], immature flowers [8] and recently from the fruits [5]. Previous studies of the composition of Eucalyptus oleosa leaves essential oil have been reported [9,15,16], but to the best of our knowledge, no previous studies on the chemistry and antioxidant and antimicrobial activities of the essential oils of stem, immature flowers and fruit of E. oleosa have been presented in the literature to date.…”
Section: Introductionmentioning
confidence: 99%
“…were richer in essential oil than those from Australia (oil yields of 0.4, 0.5, 0.6, 0.4, and 2.8%, resp.) [8] [10] [13] [17]. On the other hand, the oil yields of E. gunnii, E. viminalis, and E. bicostata from Tunisia (0.5, 2.1, and 3.0%) were lower than those from Australia (2.1, 3.6, and 3.2%) [7] [17].…”
mentioning
confidence: 99%